First-in-man feasibility study of a novel ingestible magnetically inflated balloon capsule for treatment of obesity - Kaan, Hung Leng; Phan, Phuoc Thien; Tiong, Anthony Meng Huat; Miyasaka, Muneaki; Phee, Soo Jay; Ho, Khek Yu (Endoscopy International Open, 2020)
Intragastric balloons (IGBs) are an established treatment option for obesity. Major barriers to dissemination of IGBs include lack of long-term efficacy outcomes, safety concerns, cost, and tolerability. We developed a novel ingestible magnetically inflated balloon capsule (IMI-BC) in hopes of overcoming these challenges. The IMI-BC is significantly cheaper than IGBs currently available on the market. We performed proof-of-concept animal studies and a first-in-human feasibility study to demonstrate the feasibility of inflating the IMI-BC using an external magnet. Further studies are currently being conducted to evaluate the safety, tolerability, and long-term efficacy of the IMI-BC. When fully developed, we anticipate that this device will benefit obese patients.